2019
DOI: 10.1002/ijgo.12763
|View full text |Cite
|
Sign up to set email alerts
|

Internal iliac artery balloon occlusion during cesarean hysterectomy in women with placenta previa accreta

Abstract: Objective To investigate the effect of balloon occlusion of internal iliac arteries during cesarean hysterectomy in women with placenta previa accreta. Methods Retrospective cohort study conducted using medical records of women with placenta previa and pathologically confirmed accreta taken from a single tertiary center in Chengdu, China, between January 1, 2012 and December 31, 2017. Baseline characteristics and pregnancy outcomes were compared between women with and without balloon occlusion of internal ilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…[ 7 ] However, other studies have found the opposite. [ 25 ] These studies have focused on the use of BO in traditional CS, and there are no reports on the preoperative application of BO during PTUI CS. In the study by You et al, [ 5 ] a novel technique using PTUI during CS is presented that could effectively control bleeding and preserve the uterus in patients with placenta previa and PA. Prophylactic internal IIA BO and cell salvage are increasingly being performed during PTUI CS when there is a high risk of hemorrhage in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] However, other studies have found the opposite. [ 25 ] These studies have focused on the use of BO in traditional CS, and there are no reports on the preoperative application of BO during PTUI CS. In the study by You et al, [ 5 ] a novel technique using PTUI during CS is presented that could effectively control bleeding and preserve the uterus in patients with placenta previa and PA. Prophylactic internal IIA BO and cell salvage are increasingly being performed during PTUI CS when there is a high risk of hemorrhage in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate the use of IIA BO for treatment of PA, and they found preoperative prophylactic BO was associated with reduced EBL and fewer massive donor transfusions [26] . However, other studies have found the opposite [27] . These studies have focused on the use of BO in traditional CS, and there are no reports on the preoperative application of BO during PTUI CS.…”
Section: Discussionmentioning
confidence: 83%
“…Previous randomized, controlled trials included 13 patients who were diagnosed with placenta accreta in the intervention group and 14 cases in the control group found that there were no significant differences in calculated blood loss (4950 verus 4709 mL) and PRBC units transfused (5.2 verus 4.1 U) between the intervention and control groups [ 25 , 26 ]. Chen et al compared 83 patients with placenta previa and accreta who underwent cesarean hysterectomy in the balloon group and 31 patients in the control group, they found PBOIIA had no significant effects on reducing EBL (3000 vs 3700 mL) and improving maternal outcomes [ 27 ]. These findings suggested that PBOIIA had no benefit in patients with placenta accreta.…”
Section: Discussionmentioning
confidence: 99%